Fungsi Bahasa Dilihat Dari Perspektif Fenomenologi - Lusiana Suciati Dewi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study aims to describe the perspective of language function from a phenomenological perspective, this research method is a qualitative descriptive or critical review of several linguist theories. The results of this study compare that the function of language phenomenologically always changes in every era seen from how humans think and develop according to changing times. Language as a communication tool is certainly one of the wonders of the world because of how each region or country has its own language which is very useful for exchanging information.